2012
DOI: 10.5539/ijc.v4n6p1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Zinc(II) Ion for the Formation of Iron Deposition in Human Body and Its Significance

Abstract: Iron depositions, one of the non-transferrin-bound iron (NTBI), are frequently observed for the patients with thalassemia, hemochromatosis and other iron-overloading disorders. In this article, we have pointed out that zinc(II) ion and hydrogen peroxide play a critical role in the formation of the iron deposition, and that the formation of iron deposition by zinc(II) ion should be one of the important method to protect the oxidative stress by water-soluble NTBI. This implies that the zinc(II) ions contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
(1 reference statement)
0
7
0
Order By: Relevance
“…Immediate formation of the iron deposition in the solution containing K[Fe(ida) 2 ] 3H 2 O complex (0.015 M) and albumin solution by H 2 O 2 addition strongly supports that the structure of the iron deposition formed contain di--oxo bridged dimeric Fe(III) cores as proposed (Nishida, 2012a), and also is consistent with the suggestion that alpha-synuclein acts in concert with iron and dopamine to induce formation of Levy body pathology in Parkinson's disease (PD) and cell death in PD. (O-Golts et al, 2000), and also gives reasonable explanation for the fact that -syn-Fe(III) generated from the oxidation of -syn-Fe(II) by O 2 with H 2 O 2 as a co-product, is a short-lived, dissociates to hydrolyze to ferrihydrite gel.…”
Section: Iron Deposition Formation Between Albumin and Fe(ida) Complementioning
confidence: 73%
“…Immediate formation of the iron deposition in the solution containing K[Fe(ida) 2 ] 3H 2 O complex (0.015 M) and albumin solution by H 2 O 2 addition strongly supports that the structure of the iron deposition formed contain di--oxo bridged dimeric Fe(III) cores as proposed (Nishida, 2012a), and also is consistent with the suggestion that alpha-synuclein acts in concert with iron and dopamine to induce formation of Levy body pathology in Parkinson's disease (PD) and cell death in PD. (O-Golts et al, 2000), and also gives reasonable explanation for the fact that -syn-Fe(III) generated from the oxidation of -syn-Fe(II) by O 2 with H 2 O 2 as a co-product, is a short-lived, dissociates to hydrolyze to ferrihydrite gel.…”
Section: Iron Deposition Formation Between Albumin and Fe(ida) Complementioning
confidence: 73%
“…As these polymeric iron(III) ions are not transferred to apo-transferrin (Nishida, Ito & Satoh, 2007;Nishida, 2012c), above discussion explains the marked iron accumulation in the brain as well as visceral tissue despite low serum iron levels, and under these conditions where excess hydrogen peroxide is present. It seems quite likely that highly toxic (-peroxo)diiron(III) species ((A) in Scheme I) generates in a facile manner, degrading the peripheral proteins or DNA, inducing severe oxidative damage, which are all consistent with those observed in the aceruroplasminemia patients (Yoshida, et al 2000), where in the patient of aceruroplasminemia, Fe 2+ ions are oxidized by apo-transferrin to Fe 3+ ions with the formation of hydrogen peroxide (Nishida, 2012c). Similar ferroxidase-like function was also observed for APP, amyloid precursor protein (Duce, et al 2011), and thus promoted production of APP should be closely related with the increase of AD patients as observed (Roberts, et al 2012).…”
Section: Hydrogen Peroxide and Ntbimentioning
confidence: 99%
“…This should be due to the strong electrophilicity of the (-peroxo)(-oxo)-diiron(III) species (species (A) in Scheme I) formed in the solution (Nishida, 2003(Nishida, , 2004(Nishida, , 2011(Nishida, , 2012a(Nishida, , 2012b, which turns to the di--oxo-diiron(III) species by oxidizing the methanol in the solution The further aggregation of the di--oxo-diiron(III) species may proceed to give the iron deposition (see (C) in Scheme I), because it has been pointed out that the iron deposition is the aggregation of di--oxo-diiron (III) species based on the structural properties of hydroxo(oxo)iron clusters (Nishida, 2012a(Nishida, , 2012c; this is exemplified by the recent our work (Abe, Sakiyama & Nishida, 2015a). As these polymeric iron(III) ions are not transferred to apo-transferrin (Nishida, Ito & Satoh, 2007;Nishida, 2012c), above discussion explains the marked iron accumulation in the brain as well as visceral tissue despite low serum iron levels, and under these conditions where excess hydrogen peroxide is present. It seems quite likely that highly toxic (-peroxo)diiron(III) species ((A) in Scheme I) generates in a facile manner, degrading the peripheral proteins or DNA, inducing severe oxidative damage, which are all consistent with those observed in the aceruroplasminemia patients (Yoshida, et al 2000), where in the patient of aceruroplasminemia, Fe 2+ ions are oxidized by apo-transferrin to Fe 3+ ions with the formation of hydrogen peroxide (Nishida, 2012c).…”
Section: Hydrogen Peroxide and Ntbimentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous papers, we have concluded that amyloid plaques formation is induced by zinc(II) ions in order to protect the toxicity due to non-transferrin-bound iron, and amyloid plaques are itself not toxic. (Nishida, 2012b(Nishida, , 2012c Based on the facts that iron deposition containing several proteins occurs in the presence of a Fe(III) species and hydrogen peroxide (Nishida, 2012c, 2012a, Peng et al, 2010, it is quite likely that Levy Bodies are produced through the interactions among -syn protein, iron(III) ions and hydrogen peroxide which is derived from the Nishida Reaction, and thus Levy Bodies itself are non-toxic, but at the same time of its formation serious damages to cells are induced by the strong electrophilicity of copper(II)-peroxide and/or iron(III)-peroxide adducts (Nishida, 2007(Nishida, , 2012a(Nishida, , 2012b, which should be the main origin for the observed specific loss of neurons in the brain of PD patients. The above discussion seems to be quite consistent with the suggestion that -syn acts in concert with iron and dopamine to induce formation of Levy body pathology and cell death in PD (O-Golts et al 2000).…”
Section: Toxicity Due To Oligomeric Alpha-synuclein Induced By Coppermentioning
confidence: 99%